Emotional competencies in the process of teaching and learning in nursing, from the perspective of the neurosciences Competencias emocionales en el proceso de enseñanza-aprendizaje en enfermería en la perspectiva de las neurociencias Competências emocionais no processo de ensinar e aprender em enfermagem na perspectiva das neurociências - Wilza Rocha Pereira; Mara Regina Rosa Ribeiro; Valéria Binato Santili Depes; Neuci Cunha Santos (Universidade de São Paulo, 2013)
OBJECTIVE: to investigate aspects of the interaction which occurs between feeling and learning from the perspective of the neurosciences. METHOD: research with a qualitative approach, of the case study type, undertaken in Brazilian public nursing colleges. The research subjects were lecturers and students. The techniques of use of a questionnaire, individual interviews and a focus group were used in data collection. RESULTS: knowledge of cerebral functioning and the functioning of different structures involved in the learning of cognitive, technical, emotional and relational competences can help the lecturer in her task of teaching. CONCLUSIONS: we can outline the difficulties of learning and need, as lecturers, to develop teaching strategies based in the new knowledge from the neurosciences so as to maximize the students' learning. This new knowledge brings elements which contribute to the teacher's training, facilitate the process for the person learning, and make teaching more pleasurable. OBJETIVO: comprender aspectos de la interacción que ocurre entre el sentir y el aprender en la perspectiva de las neurociencias. MÉTODO: investigación con abordaje cualitativo, del tipo estudio de caso, realizada en dos escuelas de enfermería públicas brasileñas. Los sujetos de la investigación fueron docentes y discentes; en la recolección de datos empleamos las técnicas del cuestionario, entrevista individual y grupo de enfoque. RESULTADOS: los conocimientos del funcionamiento del cerebro y diferentes estructuras implicadas en los aprendizajes de las competencias cognitivas, técnicas, emocionales y relacionales pueden ayudar al docente en su tarea de enseñar. CONCLUSIONES: pudimos contornar las dificultades para aprender y precisamos, como docentes, desarrollar estrategias de enseñanza basadas en los nuevos conocimientos de las neurociencias, para optimizar el aprendizaje de los alumnos. Estos nuevos conocimientos contienen elementos que contribuyen con la formación del profesor, facilitan el proceso para aquel que aprende y torna más agradable el enseñar. OBJETIVO: compreender aspectos da interação que ocorre entre o sentir e o aprender na perspectiva das neurociências. MÉTODO: pesquisa com abordagem qualitativa, do tipo estudo de caso, feita em duas escolas de enfermagem públicas brasileiras. Os sujeitos da pesquisa foram docentes e discentes e, na coleta de dados, empregaram-se as técnicas do questionário, entrevista individual e grupo focal. RESULTADOS: os conhecimentos do funcionamento cerebral e diferentes estruturas implicadas nos aprendizados das competências cognitivas, técnicas, emocionais e relacionais podem ajudar o docente na sua tarefa de ensinar. CONCLUSÕES: pode-se contornar as dificuldades para aprender e é necessário, como docente, desenvolver estratégias de ensino baseadas nos novos conhecimentos das neurociências, para otimizar a aprendizagem dos alunos. Esses novos conhecimentos trazem elementos que contribuem para a formação do professor, facilitam o processo para aquele que aprende e tornam mais prazeroso o ensinar.